DRC™ ICP-MS coupled with automated flow injection system with anion exchange minicolumns for determination of selenium compounds in water samples - Kritsana Jitmanee (2018)
A flow injection system with anion exchange resin minicolumns was coupled with dynamic reaction cell (DRC™) ICP-MS for the determination and speciation of selenite and selenate at sub μg L-1levels. The charged selenate and uncharged selenite were separated on the first resin column in which only selenate was retained. The unretained selenite was then deprotonated with alkaline solution, and the resulting anionic selenite species was collected on the second column serially connected downstream. By setting a sample loop, total selenium can be determined together with selenite and selenate. The selenium species was eluted by nitric acid and carried to DRC™ ICP-MS for their detection. Using ammonia as reaction gas, the detection of78Se was improved. The enrichment factor was 20 for 10 mL of sample. The standard deviations (n = 5) of peak heights were 4.9%, 4.1%, and 7.0% for a 5.0 × 10-2μg L-1selenite and selenate, and total Se, respectively. The calibration graphs were linear from 2.0 × 10-2to 1.0 μg L-1selenite and selenate. And, the linearity for total selenium was good in the range of 10.0 × 10-2to 1.0 μg L-1. The proposed method has been demonstrated for the application to natural and bottled drinking water samples. © 2007 Elsevier B.V. All rights reserved.